A CAD-CAM Evaluation of Maxillary Canine Retraction Using Two Different Modalities with MBT Prescription-An In Vivo Study - Jacob, George Jeryn (The Journal of Dentists, 2015)
Objective: (1) To measure and compare the amount of maxillary canine retraction. (2) To compare the rate of maxillary canine retraction. Materials and Methods: This was a split mouth design study to compare the amount of maxillary canine retraction using two different modalities. The two modalities of maxillary canine retraction were conventional mechanics with E-chain extending from molar to maxillary canine on one side and the other modality was using orthodontic microimplants loaded with E-chain to the maxillary canine. The sample comprised 15 patients (9 male, 6 female, mean age 19.8 years; range 16-25 years) who were scheduled for extraction of all the upper first premolar. A brass wire guide and a peri-apical radiograph were used to determine the microimplant position. Titanium orthodontic microimplants 1.3 mm in diameter and 10 mm in length were placed between the roots of the second premolar and the first molar of the maxillary arch. After 15 days, the microimplants and the molars were loaded with continuous elastomeric chains expressing 150 grams for canine retraction. Pre-retraction and post-retraction study models were taken for measuring the amount of retraction. Study models were scanned and assessed using CAD-CAM. Results: The total space closure on the molar anchor side was 4.62 mm (1.1 mm contributed by mesial molar movement) and microimplant anchor side was 4.12 mm. The rate of canine retraction on the molar anchor was 1.07 mm/month and 0.91 mm/month on the microimplant anchor side. Conclusion: The amount and rate of canine retraction is similar when proceeded with a conventional or a microimplant supported canine retraction.